ANALISIS PERHITUNGAN, PENYETORAN, PELAPORAN DAN PENCATATAN PPN PADA PT.X TAHUN 2022 - Angeline, Angeline; Sukadana, Ida Bagus Nyoman (E-Jurnal Akuntansi TSM, 2023)
The purpose of this research was to analyse the appropriateness of the procedures for calculating, depositing, reporting and recording of Value Added Tax carried out by PT.X with Law No. 42 of 2009 in conjunction with Law No. 7 of 2021 (HPP ) and knowing if the jurnal record has been carried out according to accounting standard. The research method used in this research is the descriptive analysis method. In this research, the supporting documents used were obtained directly from PT.X in the form of secondary data consisting of Output Tax Invoice, Input Tax Invoice, Periodical VAT Return Report, Tax Payment Slip and E-Receipt of Tax Reporting, as well as primary data in the form of interviews. The results of this research prove that the procedures for calculating, depositing, reporting and recording Value Added Tax carried by PT.X are in accordance with Law No. 42 of 2009 in conjunction with Law No. 7 of 2021 (HPP) and applicable accounting principles.